The Role and Function of The Financial Services Authority in The Supervision and Protection of Consumers against Illegal Online Loans - Yenny Ratnasari; Febby Mustikasari; Ichsandi Naufal Putra Perdana; Alvyan Miftahul Huda; Narendra Khairafi Cahyandi; Tania Shapna Putri (Universitas Muhammadiyah Surakarta, 2023)
This journal with the title